Regulation of chemicals demands assessment of risks rather than identification of hazards only - P. Marx-Stoelting; V. Ritz; M. Herzler; C. Kneuer; K. Aiello-Holden; S Brescia; S. E. Escher; S. Feustel; E. Fritsche; J. Gebel; E. F. Kenny; R. Landsiedel; et al. (Archives of Toxicology, 2026)
This position paper was collaboratively written during the international expert symposium “EU Chemicals Assessment - Risk- or Hazard-based?” that was organised by the German Federal Institute for Risk Assessment (BfR) in Berlin on November 27th and 28th 2025. Twenty experts from several institutions and European countries considered the scientific merits of both hazard-based and risk-based approaches to chemical safety assessment. While hazard information is essential, it does not reflect real-world exposure conditions that determine the likelihood of harm. On balance, we support a risk-based approach because it enables more proportionate, transparent and scientifically grounded regulatory decisions.

Report on the European Partnership for Alternative Approaches to Animal Testing (EPAA) “New Approach Methodology (NAMs) User Forum”, 30–31 October 2024, Helsinki, Finland - Mark T.D. Cronin; Sophie Cable; Christian Desaintes; Sylvia E. Escher; Ellen Hessel; Ellen Fritsche; Petra Kern; Gavin Maxwell; Gladys Ouedraogo; Tomasz Sobanski; Matthias Wehr; Andrew White (Regulatory Toxicology and Pharmacology, 2026)

CEC02-01 Brief Session Introduction on DNT - E. Fritsche (Toxicology Letters, 2025)

P28-27 Developmental Neurotoxicity as a Case Example for a Six-Step Framework for the Sustainable Regulatory Implementation of NAMs - J. Blum; K. Bartmann; J. de Paula Souza; E. Fritsche (Toxicology Letters, 2025)

P18-67 Regulation of key neurodevelopmental processes by disease pathways and nuclear receptors in a human Neurosphere Assay - E. Kuchovska; K. Koch; K. Bartmann; K. Schluppmann; A. Donmez; J. Klose; G. Raad; M. Schade; L.-C. Saborowski; E. Fritsche (Toxicology Letters, 2025)

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

P18-51 Advancing in vitro Developmental Neurotoxicity (DNT) screening: Expanding the biological coverage of the DNT in vitro battery (IVB) by integration of glial cell-related endpoints - A.S. Cheruvil lilikumar; E. Zühr; R. Guzzo; E. Fritsche; K. Koch (Toxicology Letters, 2025)

P30-79 Bridging Mechanistic Neurotoxicity Testing and Regulatory Application with Human-Relevant NAMs within CHIASMA - R. Roy Chowdhury; I. Scharkin; E. Fritsche; K. Koch (Toxicology Letters, 2025)

P30-76 Linking hormone receptor signaling to neurodevelopmental disruption: Advancing EDC hazard assessment using human-based DNT in vitro models - K. Koch; K. Schlüppmann; L.M. Stark; A. Dönmez; E. Fritsche (Toxicology Letters, 2025)

P30-70 Application of human-based 2D and 3D new approach methodologies for assessing developmental and adult neurotoxicity (DNT and ANT) in vitro - J. Klose; K. Bartmann; F. Bendt; A. Dönmez; K. Koch; E. Zuehr; A. Mosig; E. Fritsche (Toxicology Letters, 2025)

P28-04 Towards Animal-Free DIT Testing: Establishing a Human Stem Cell-Based Assay for Early Hematopoiesis - C. Spruck; A. Bartel; G. Brockerhoff; S. Fayyaz; Q. Li; F.A. Grimm; E. Fritsche; K. Koch; J. Tigges (Toxicology Letters, 2025)

P03-09 Establishment of Readiness Criteria for AI-based tools for risk assessment: READYAI - J. de Paula Souza; J. Blum; L. Wendt-Rasch; U. Maran; S. Sild; R. Lee; A. Čavoški; L. Holden; L. Dawson; G. Rivière; E. Di Consiglio; O. Tcheremenskaia; et al. (Toxicology Letters, 2025)

CEC02-04 Science and use of the current DNT in vitro battery - E. Fritsche (Toxicology Letters, 2025)

P14-15 Species-, Cell Type- and Developmental-Specific Variability in DNA Repair Capacities of Human and Rodent Neural Progenitor Cells - L.P. Czernik; M. Pahl; L. Dittmann; E.R. de Caro; L.M. Stark; E. Fritsche; J. Tigges; K. Koch (Toxicology Letters, 2025)

Correction: Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2025)

P19-70 Gaps and needs analysis, barriers, opportunities and drivers for implementation of Artificial Intelligence and Machine Learning (AI/ML) tools in regulatory risk assessment - S. Kolesnyk; A. Bearth; N. Roth; E. Fritsche; M.F. Wilks (Toxicology Letters, 2024)

P09-21 Oligodendrocyte development as a crucial key event for developmental neurotoxicity - E. Fritsche; K. Koch (Toxicology Letters, 2024)

P05-45 Ontology maps: data integration tools for applications in toxicology - B. Staumont; L. Ladeira; A. Gamba; A. Verhoeven; J. Sanz Serrano; E. Kuchovska; J. Berkhout; D. A.; M. Teunis; T.H. Luechtefeld; T. Hartung; R. Jover; et al. (Toxicology Letters, 2024)

OS04-05 Addressing uncertainties in the DNT in vitro battery (DNT IVB) by incorporating glial models and increasing human relevance - K. Koch; E. Zühr; K. Bartmann; R. Guzzo; A.S. Cheruvil Lilikumar; L. Stark; I. Egger; O. Myhre; E. Fritsche (Toxicology Letters, 2024)

OS02-03 Using a systems biology approach to construct adverse outcome pathway networks aligned with the FAIR principles - L. Ladeira; A. Mazein; M. Ostaszewski; A. Verhoeven; E. Kuchovská; J. Sanz-Serrano; A. Drees; K. Reiche; K. Sewald; E. Fritsche; M. Vinken; L. Geris; et al. (Toxicology Letters, 2024)

OS01-06 Human-based New Approach Methodologies for developmental and adult neurotoxicity testing in vitro - K. Bartmann; F. Bendt; A. Dönmez; J. Klose; K. Koch; E. Fritsche (Toxicology Letters, 2024)

S05-01 Functional mapping of neurodevelopmental disorders to ontology-based DNT NAMs for Next Generation Risk Assessment of chemicals - E. Kuchovska; L. Ladeira; K. Bartmann; D. Polozij; N. Gorts; E. Corek; A. Donmez; L.-C. Saborowski; F. Bendt; M. Schade; G. Raad; A. Gamba; et al. (Toxicology Letters, 2024)

Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2024)
Zinc (Zn) biofortification of rice can address Zn malnutrition in Asia. Identification and introgression of QTLs for grain Zn content and yield (YLD) can improve the efficiency of rice Zn biofortification. In four rice populations we detected 56 QTLs for seven traits by inclusive composite interval mapping (ICIM), and 16 QTLs for two traits (YLD and Zn) by association mapping. The phenotypic variance (PV) varied from 4.5% ( qPN 4.1 ) to 31.7% ( qPH 1.1 ). qDF 1.1 , qDF 7.2 , qDF 8.1 , qPH 1.1 , qPH 7.1 , qPL 1.2 , qPL 9.1, qZn 5.1 , qZn 5.2 , qZn 6.1 and qZn 7.1 were identified in both dry and wet seasons; qZn 5.1 , qZn 5.2 , qZn 5.3, qZn 6.2, qZn 7.1 and qYLD 1.2 were detected by both ICIM and association mapping. qZn 7.1 had the highest PV (17.8%) and additive effect (2.5 ppm). Epistasis and QTL co-locations were also observed for different traits. The multi-trait genomic prediction values were 0.24 and 0.16 for YLD and Zn respectively. qZn 6.2 was co-located with a gene ( OsHMA2 ) involved in Zn transport. These results are useful for Zn biofortificatiton of rice.

LP-24: The Cognitive Function Defects Ontology: Integrating Biological, Toxicological, and Chemical Data for Next-Generation Risk Assessment - L.C. Maia Ladeira; E. Kuchovská; N. Görts; T. Hofer; O. Myhre; G.L.S. Lopez Soop; H. Dirven; A. Gamba; R. Lesage; E. Fritsche; L. Geris; B. Staumont (Toxicology Letters, 2023)

P22-35: Mapping of DNT NAMs’ signaling pathways in human physiology and disease for regulatory application - E. Kuchovska; K. Bartmann; L. C. Maia Ladeira; A. Dönmez; L.-C. Saborowski; F. Bendt; M. Schade; G. Raad; R. Lesage; A. Gamba; B. Staumont; L. Geris; et al. (Toxicology Letters, 2023)

P21-14: Neurodevelopmental toxicity of T-2 mycotoxin in human-based primary and induced pluripotent stem cell-derived neural progenitor cells in 3D and 2D - M. Taroncher Ruiz; J. Kapr; K. Bartmann; J. Tigges; Y. Rodriguez-Carrasco; M.J. Ruiz; E. Fritsche (Toxicology Letters, 2023)

P16-10: Refinement of an in vitro testing battery for developmental neurotoxicity assessment by integration of radial glia- and astrocyte-specific endpoints - E. Zühr; K. Koch; E. Fritsche (Toxicology Letters, 2023)

P16-08: Development of the NPC1_RAR_GR assay to identify putative endocrine disrupting chemicals (EDCs) disturbing glucocorticoid receptor (GR) or retinoic acid receptor (RAR) signaling in vitro - K. Schlüppmann; S. Hüsken; L. Stark; A. Dönmez; N. Förster; K. Koch; E. Fritsche (Toxicology Letters, 2023)

P09-34: Unraveling hormonal dependencies and associated species-specificities of neurodevelopmental key events to improve EDC risk assessment - K. Koch; K. Schlüppmann; S. Hüsken; L. Stark; S. Masjosthusmann; J. Klose; N. Förster; A. Dönmez; E. Fritsche (Toxicology Letters, 2023)

OS03-02: Comparative analysis of human and rat neural stem-/progenitor cell functions during developmental time-dependent genotoxin exposure in vitro - M. Pahl; J. Klose; E. Fritsche (Toxicology Letters, 2023)

S10-02: AOPs for Neurotoxicity - E. Fritsche (Toxicology Letters, 2023)

Serendipita restingae sp. nov. (Sebacinales): an orchid mycorrhizal agaricomycete with wide host range - Yohan Fritsche; Morgana E. Lopes; Marc-André Selosse; Valdir M. Stefenon; Miguel P. Guerra (Mycorrhiza, 2021)

Increasing accuracy and reducing costs of genomic prediction by marker selection - Massaine Bandeira e Sousa; Giovanni Galli; Danilo Hottis Lyra; Ítalo Stefanini Correia Granato; Filipe Inácio Matias; Filipe Couto Alves; Roberto Fritsche-Neto (Euphytica, 2019)

Modeling copy number variation in the genomic prediction of maize hybrids - Danilo Hottis Lyra; Giovanni Galli; Filipe Couto Alves; Ítalo Stefanine Correia Granato; Miriam Suzane Vidotti; Massaine Bandeira e Sousa; Júlia Silva Morosini; José Crossa; Roberto Fritsche-Neto (Theoretical and Applied Genetics, 2019)

International STakeholder NETwork (ISTNET): creating a developmental neurotoxicity (DNT) testing road map for regulatory purposes - Anna Bal-Price; Kevin M. Crofton; Marcel Leist; Sandra Allen; Michael Arand; Timo Buetler; Nathalie Delrue; Rex E. FitzGerald; Thomas Hartung; Tuula Heinonen; Helena Hogberg; Susanne Hougaard Bennekou; et al. (Archives of Toxicology, 2015)

A prevalent POLG CAG microsatellite length allele in humans and African great apes - Anja T. Rovio; Josef Abel; Arja L. Ahola; Aida M. Andres; Jaume Bertranpetit; Antoine Blancher; Ronald E. Bontrop; Leona G. Chemnick; Howard J. Cooke; James M. Cummins; Heidi A. Davis; David J. Elliott; et al. (Mammalian Genome, 2004)